SENSATIONAL UNKNOWN FACTS FROM GEORGIAN DIPLOMACY OF 90-IES OF XVIII CENTURY - Mamuka Natsvaladze (International Journal of Innovative Technologies in Social Science, 2020)
The Italian translation of Erekle the Second’s letter maintained in the archive of Vienna which was published in 1979 by Professor Ilia Tabaghua, reveals a sensational secret. In this letter we found a unique delf unveiling the fact that after the Krtsanisi tragedy suffered in 1795 Erekle the Second addressed Europe.In the course of studies and analyses we came across several delfs in one document that had been considered to be one letter, namely, in the Italian translation of a letter by Erekle the Second; chronologically these delfs turned out to be significantly distant from one other. Further studies conducted on these delfs brought us to the conclusion that in 1795, after the Krtsanisi tragedy, Erekle the Second’s ambassadors arrived to Vienna and handed the letter to the Emperor of Austria.In the Italian translation of a document by Erekle the Second that had been considered by scientists to be one single letter and which is dated with 1782, the fragment saying that “in these days the king’s residence in the East was totally destroyed” caused the first suspicion. We want to especially underline the circumstance that there is no evidence of destruction of any city or a town what could be considered to be the eastern residence of the king, found in the 80-s of the XVIII century. Therefore, there is only one way left – we should accept it that Erekle the Second is speaking about the fact of Agha Mohammad Khan destroying Tbilisi in 1795 – the tragedy that took place 13 years later. It is another fact that in 1782 Erekle the Second had no means to write about the events that would have taken place in 1795.And thus, we have come to the conclusion that the Italian translation of the letter by Erekle the Second prepared by the chancellery of the Emperor of Austria based upon the letter sent by Erekle, is not a single letter but a compilation of at least two letters written by him. We should give due significance to the fact that the mentioned Italian translation does not contain any specific personalized addressee but is addressed to the Emperor of Austria, not revealing to which of the Emperors it addresses namely. The translation does not contain any concrete date either. The article provides review of the purposes and goals that the ambassadorial mission of late fall of 1795 sent by the king Erekle to the Emperor of Austria as well as other delfs of the above mentioned letter that cause suspicion and that unambiguously confirm it that certain fragments of the letter are written in 1795 which on its part implies confirmation of the fact that in the late fall of the year 1795 there had place a diplomatic communication between the Austrian Empire and the Kingdom of Kartli and Kakheti.This latter fact abolishes the view that had been established in historiography up today that Erekle the Second unconventionally turned to Russia after Agha Mohammad Khan brought Tbilisi to earth in 1795.